Idiopathic inflammatory myopathy: Interrater variability in muscle biopsy reading. (27th August 2019) - Olivier, Pieter A.; De Paepe, Boel; Aronica, Eleonora; Berfelo, Florieke; Colman, Roos; Amato, Anthony; Dimitri, Dalia; Gallardo, Eduard; Gherardi, Romain; Goebel, Hans-Hilmar; Hilton-Jones, David; Hofer, Monika; et al.
Abstract : Objective: To determine interrater variability in diagnosing individual muscle biopsy abnormalities and diagnosis. Methods: We developed a scoring tool to analyze consensus in muscle biopsy reading of an ad hoc workgroup of international experts. Twenty-four samples from patients with suspected idiopathic inflammatory myopathy (IIM) were randomly selected, providing sections that were stained with standard histologic and immunohistochemical methods. Sections were made available on an online platform, and experts were queried about myopathologic features within 4 pathologic domains: muscle fibers, inflammation, connective tissue, and vasculature. A short clinical presentation of cases was included, and experts were asked to give a tentative diagnosis of polymyositis, dermatomyositis, inclusion-body myositis, antisynthetase syndrome–related myositis, immune-mediated necrotizing myopathy, nonspecific myositis, or other disease. Fleiss κ values, scoring interrater variability, showed the highest agreement within the muscle fiber and connective tissue domains. Results: Despite overall low κ values, moderate agreement was achieved for tentative diagnosis, supporting the idea of using holistic muscle biopsy interpretation rather than adding up individual features. Conclusion: The assessment of individual pathologic features needs to be standardized and harmonized and should be measured for sensitivity and specificity for subgroup classification. Standardizing the process of diagnostic muscle biopsy reading would allow identification of more homogeneous patient cohorts for upcoming treatment trials.